Reliability in somatic cell count measurement of clinical mastitis milk using DeLaval cell counter - Kawai, Kazuhiro; Hayashi, Tomohito; Kiku, Yoshio; Chiba, Tomoyuki; Nagahata, Hajime; Higuchi, Hidetoshi; Obayashi, Tetsu; Itoh, Seigo; Onda, Ken; Arai, Sachiko; Sato, Reiichiro; Oshida, Toshio (Animal science journal, 2013)
Somatic cell counts (SCC) measurements are typically performed using quantitative methods, such as the Breed method (Breed) and the Fossomatic method (FSCC). The DeLaval cell counter (DCC) developed recently is a quantitative somatic cell counter with a low initial cost and superior portability. However, since the DCC was specifically developed for measuring SCC of ≤ 4 × 106 cells/mL milk from bulk tanks or individual cows, its reliability for estimating SCC that exceed this concentration has not yet been clarified. This study therefore examined whether it is possible to accurately measure SCC by diluting milk samples with initial SCC of 4 × 106 cells/mL, as seen in clinical mastitis milk. We collected milk samples from 99 quarters of 99 Holstein cows with clinical mastitis. These milk samples were diluted 10‐fold with saline and thoroughly mixed before performing SCC measurement with the DCC. The correlation coefficients of SCC measured by the FSCC, Breed and DCC methods indicated strong correlations between each pair of methods. The findings showed that DCC can be used to identify bovine clinical mastitis milk and is useful as a quantitative SCC measurement device on farm sites.